ANALYSIS OF COST STRUCTURE, REVENUE, AND PROFITABILITY OF TOFU PRODUCTION BUSINESS (CASE IN WAHYU UTAMA UKM, GUNUNG PUTRI, BOGOR REGENCY) - Siti Rochaeni; Rizky Adi Puspita Sari; Desita Prastiwi (Syarif Hidayatullah State Islamic University Jakarta, 2022)
Tofu is one of the popular processed soybean products for the people of Indonesia. Wahyu Utama UKM is one of the medium-scale tofu processing industries in Bogor Regency , with tofu products sold are white tofu consisting of small tofu products and big tofu products. Wahyu Utama UKM, which has been operating since 2018, unfortunately does not have a systematic cost recording, does not know the income that has been obtained, has not done calculations The efficiency of its business, and also faced with the sales of tofu products in TahuN 2021 which tends to decline. The objectives of this study are (1) Analyzing the cost structure of Wahyu Utama SMEs in producing tofu; (2) Analyzing the income of tofu production business in Wahyu Utama SMEs; (3) Analyzing the level of B/C Ratio, Break Even Point (BEP), and Payback Period (PP) in tofu production businesses in Wahyu Utama SMEs; (4) Analyze the profitability of tofu production business in Wahyu Utama SMEs. The research was conducted at Wahyu Utama UKM, Bogor Regency . Types of quantitative research with descriptive analysis. The data source uses primary data and secondary data. The data analysis used is descriptive analysis to find out the general description of the company, business cost structure, business revenue analysis to measure revenue , and revenue, followed by business analysis with B/C Ratio, Break Even Point (BEP), and Payback Period (PP), as well as business profitability analysis with Margin of Safety (MOS) and Marginal Income Ratio (MIR). The results showed that (1) The variable costs needed by Wahyu Utama SMEs have a higher percentage compared to fixed costs, as for the largest cost component to produce small tofu products and big tofu products are the cost of purchasing soybeans, while the smallest cost component isthe cost of land and building taxes; (2) The business revenue of tofu products in Wahyu Utama SMEs in 2021 was IDR 1,234,274,167 which came from the income of small tofu products of IDR 675,788,202 and large tofu products of IDR 558,485,965; (3) The value of the B/C Ratio in small tofu products is 0.19 and in large tofu products which is 0.15, the result of the B/C Ratio value obtained in small tofu products and big tofu products has been reaching a number of more than zero, so it can be said that the tahu production business in Wahyu Utama SMEs is profitable or provides benefits; sales volume and product receipts know that Wahyu Utama SMEs are already greater than the calculation of the Break Even Point (BEP) value, so it can be said that the tofu production business in Wahyu Utama SMEs is profitable; the Payback Period (PP) value of Wahyu Utama SME tofu production business is 0.76, which means that Wahyu Utama SMEs experience a return of capital within 9 months and 4 days; (4) The profitability obtained from the small tofu product business is 16.38 percent, and the big tofu product is 13.08 percent. This shows that the Wahyu Utama SME tofu product business has good prospects to be cultivated and developed because it generates profits.